All-organic heterostructure piezoelectric polymer composite material as well as preparation method and application thereof
By epitaxially growing two-dimensional PCL crystals on the surface of nylon 11 nanofibers and inducing piezoelectric crystal phases, the problem of existing piezoelectric polymer materials losing flexibility when improving piezoelectric output performance is solved, and high sensitivity characteristics are achieved And all-organic heterostructure piezoelectric polymer composite materials with excellent piezoelectric properties, suitable for applications in a variety of electronic equipment.
Patent Information
- Application Number
- CN202311487375.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-09
- Publication Date
- 2025-02-14
AI Technical Summary
While improving the piezoelectric output performance, existing piezoelectric polymer materials often require high-temperature and high-pressure processing conditions, and are prone to loss of flexibility, limiting their application in fields such as flexible pressure sensing and energy collection.
Using all-organic heterostructured piezoelectric polymer composite materials, two-dimensional sheet polycaprolactone (PCL) crystals epitaxially grow on the surface of nylon 11 nanofibers, and using acid solvents to induce the formation of piezoelectric crystal phases inside the fibers to form Excellent piezoelectric properties and flexibility.
It realizes the improvement of the piezoelectric output performance and sensitive characteristics of the material without losing flexibility. It is suitable for energy harvesting and self-powered wireless detection of fine physiological movements, and has the power in wearable and portable electronic devices in the Internet of Things Application potential.
Smart Images

Figure CN119451543A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of piezoelectric polymer composite materials, and in particular relates to a full-organic heterostructure piezoelectric polymer composite material and a preparation method and application thereof. Background Art
[0002] Traditional inorganic piezoelectric materials such as piezoelectric ceramics (e.g., zinc oxide, barium titanate) have excellent piezoelectric properties, but have some inherent defects, such as the need for high-temperature processing, high rigidity and brittleness, and poor mechanical tolerance when deformed by force, which limits their application in flexible pressure sensing and energy harvesting. In contrast, the preparation process of piezoelectric polymer materials is relatively environmentally friendly, with high flexibility and plasticity, and can accurately respond to small pressure changes. They have better adaptability to the curved morphology of organisms and have great application potential in mechanical energy harvesting and sensing. However, compared with inorganic piezoelectric materials, the piezoelectric output performance generated by intrinsic piezoelectric polymers is lower, which brings severe challenges to this field. At the same time, with the increasing miniaturization and wearability of energy harvesting devices and self-powered electronic devices, it is of great significance to develop all-organic polymer piezoelectric materials with high performance while maintaining their flexibility and lightness.
[0003] Commonly used methods to enhance piezoelectric performance (such as mechanical stretching, melt quenching, and the introduction of inorganic nanofillers) can improve the piezoelectric output performance of polymers to a certain extent, but the processing conditions are harsh and often require high temperature, high pressure, or the introduction of rigid fillers, which greatly limits the large-scale assembly and application of devices. At the same time, the above methods usually sacrifice the flexibility of the material, are costly, and are also highly toxic to the environment and the human body, which is not conducive to the development of wearable, environmentally friendly, and cost-effective energy harvesting and sensing devices. In order to solve the problem of enhancing piezoelectric performance while maintaining material flexibility, effective geometric structure design of existing piezoelectric polymer materials is a very effective solution.
[0004] At present, strategies for enhancing the piezoelectric properties of piezoelectric polymers based on geometric structure design have been reported. Generally, constructing geometric structures such as micrometer columns, nanowires, and porous structures in materials can promote the improvement of piezoelectric output and sensitivity of materials, and is an effective method for developing flexible wearable energy harvesting and sensors. However, on the one hand, the technical routes for these geometric structure designs are complex and usually require the use of templates with special structures; on the other hand, these methods usually only consider the formation of the macroscopic structure of the material, and often ignore the control of the microscopic piezoelectric crystals inside the material, which is not conducive to improving the piezoelectric properties of the material. The essence of the piezoelectric properties of the material depends on the dipole deformation and polarization of the internal piezoelectric crystal phase under the action of external force, thereby releasing the charge. Therefore, a universal, mild and low-cost piezoelectric polymer structure design method is needed to simultaneously control the formation of its macroscopic and microscopic structures, which is of great significance to improving the piezoelectric output performance of piezoelectric polymers. Summary of the invention
[0005] In view of the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide an all-organic heterostructure piezoelectric polymer composite material and a preparation method and application thereof. The all-organic heterostructure piezoelectric polymer composite material does not require the addition of any inorganic material. The material has excellent sensitivity without losing flexibility, and the material also contains piezoelectric crystals at the microscopic scale, thereby having excellent piezoelectric properties, showing outstanding performance in energy collection and self-powered wireless detection of subtle physiological movements, and showing strong application potential in wearable and portable electronic devices of the Internet of Things.
[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions: A fully organic heterostructured piezoelectric polymer composite material comprises nylon 11 nanofibers and two-dimensional sheet-like polycaprolactone (PCL) crystals epitaxially grown on the surface of the nylon 11 nanofibers. The nylon 11 nanofibers contain piezoelectric crystal phases, and the content of the piezoelectric crystal phases in the fiber crystal structure is 70-90 wt%.
[0007] The preparation method of the all-organic heterostructure piezoelectric polymer composite material comprises the following steps: (1) Preparation of nylon 11 nanofibers; (2) Heat and dissolve polycaprolactone (PCL) pellets in an acidic solvent to obtain a culture solution with a concentration of 0.1-5 wt%; at room temperature, place nylon 11 nanofibers in the culture solution for self-assembly for 3-10 min (there is no special requirement for the amount of culture solution, as long as the culture solution completely submerges the nylon 11 nanofibers), and dry to obtain an all-organic heterostructure piezoelectric polymer composite material.
[0008] Preferably, the acidic solvent is a mixed solvent of acetic acid and water in a volume ratio of (1-3):1.
[0009] Preferably, the temperature for heating and dissolving is 50-80°C.
[0010] Preferably, the drying is vacuum drying.
[0011] Preferably, the nylon 11 nanofibers are prepared by electrospinning or template method.
[0012] Preferably, the preparation process of the electrospinning method is: completely dissolving nylon 11 pellets in an organic solvent to obtain a spinning solution, and using an electrospinning device to prepare nylon 11 nanofibers.
[0013] Preferably, the organic solvent is a mixed solvent of trifluoroacetic acid and hexafluoroisopropanol in a volume ratio of (1-2):1; the spinning solution concentration is 5-10 wt%.
[0014] Preferably, the spinning solution is extruded at a rate of 0.1-1.0 mL / h in an electrospinning device, the applied voltage is 10-15 KV, the distance between the spinneret and the collector is 10-20 cm, and the nylon 11 nanofibers are collected using a high-speed roller with a rotation speed of 2000-5000 r / min; the internal ambient temperature of the spinning device is 20-30 °C and the humidity is 30-40%.
[0015] The all-organic heterostructure piezoelectric polymer composite material is used in pressure sensors, nanogenerators, wearable electronic devices or motion monitoring equipment.
[0016] The principle of the preparation method of the present invention is as follows: a piezoelectric polymer composite material with high sensitivity is obtained by epitaxially growing PCL molecules on the surface of one-dimensional nylon 11 nanofibers into two-dimensional polymer crystals, and at the same time, the protonation of nylon 11 by the acidic solvent during the assembly process is used to induce the formation of a piezoelectric crystal phase inside the nylon 11 nanofibers.
[0017] Beneficial effects: The preparation method of the present invention can not only realize the controllable preparation of highly sensitive piezoelectric polymer composites, but also simultaneously promote the formation of piezoelectric crystals, thereby avoiding the sacrifice of the flexibility of the composite materials; in addition, the two-dimensional polymer crystals produce a cross-linking effect on the one-dimensional nanofibers through interfacial interactions, thereby forming an interlaced nanofiber network inside the composite system, which has good service stability, and provides a general strategy for designing high-performance flexible all-organic polymer piezoelectric devices. This method can also be extended to other piezoelectric polymers, thereby opening up new avenues for the development of next-generation flexible pressure sensors, piezoelectric energy harvesting devices, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a scanning electron microscope image of the nylon 11 nanofiber prepared in Example 1.
[0019] Figure 2 Shown are the X-ray diffraction patterns of acid-treated and non-acid-treated nylon 11 nanofibers and ordinary nylon 11 films.
[0020] Figure 3 This is a scanning electron microscope image of the all-organic heterostructure piezoelectric polymer composite material prepared in Example 4.
[0021] Figure 4 The differential scanning calorimetry spectra of acid-treated and non-acid-treated nylon 11 nanofibers and the all-organic heterostructure piezoelectric polymer composite materials prepared in Examples 2-4 are shown.
[0022] Figure 5 It is a piezoelectric signal diagram of a piezoelectric device prepared based on the nylon 11 nanofiber of Example 1 and the all-organic heterostructure piezoelectric polymer composite material of Examples 2-4.
[0023] Figure 6 The sensitivity of the piezoelectric device prepared based on the all-organic heterostructure piezoelectric polymer composite material of Example 4.
[0024] Figure 7 The service stability of the piezoelectric device prepared based on the all-organic heterostructure piezoelectric polymer composite material of Example 4. DETAILED DESCRIPTION
[0025] In order to make the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0026] Example 1
[0027] Preparation of nylon 11 nanofibers: 0.78 g of nylon 11 pellets were completely dissolved in 10 mL of a mixed solution of trifluoroacetic acid (TFA) and hexafluoroisopropanol (HFIP) (volume ratio of 1:1) to obtain a spinning solution with a concentration of 5 wt%. The spinning solution was extruded at a speed of 0.3 mL / h in an electrospinning device. The applied voltage was 13 KV, the distance between the spinneret and the collector was 15 cm, and the fibers were collected using a high-speed roller (rotation speed of 2800 r / min). The internal ambient temperature of the spinning device was 25 °C and the humidity was 30~40%.
[0028] Example 2
[0029] Preparation of all-organic heterostructure piezoelectric polymer composite materials: 0.04 g PCL pellets were added to a mixed solution of 40 mL acetic acid and deionized water (volume ratio of 3:1), and magnetically stirred at 70 °C oil bath temperature for 3 h until it was completely dissolved to obtain a culture solution with a mass fraction of 0.1 wt%; at room temperature, the nylon 11 nanofibers prepared in Example 1 were placed in the culture solution for cultivation and taken out after 5 min. In this process, the acetic acid molecules induced the internal crystalline phase of the nylon 11 nanofibers to transform from a non-piezoelectric crystalline phase to a piezoelectric crystalline phase through protonation. Subsequently, the samples were dried in vacuum for 24 h to obtain an all-organic heterostructure piezoelectric polymer composite material, and the sample was marked as 0.1 wt%.
[0030] Example 3
[0031] Preparation of all-organic heterostructure piezoelectric polymer composite materials: 0.42 g PCL pellets were added to a mixed solution of 40 mL acetic acid and deionized water (volume ratio of 3:1), and magnetically stirred at 70 °C oil bath temperature for 3 h until it was completely dissolved to obtain a culture solution with a mass fraction of 1.0 wt%; at room temperature, the nylon 11 nanofibers prepared in Example 1 were placed in the culture solution for cultivation and taken out after 5 min. In this process, the acetic acid molecules induced the internal crystalline phase of the nylon 11 nanofibers to transform from a non-piezoelectric crystalline phase to a piezoelectric crystalline phase through protonation. Subsequently, the samples were dried in vacuum for 24 h to obtain an all-organic heterostructure piezoelectric polymer composite material, and the sample was marked as 1.0 wt%.
[0032] Example 4
[0033] Preparation of all-organic heterostructure piezoelectric polymer composite materials: 2.1 g PCL pellets were added to a mixed solution of 40 mL acetic acid and deionized water (volume ratio of 3:1), and magnetically stirred at 70 °C oil bath temperature for 3 h until it was completely dissolved to obtain a culture solution with a mass fraction of 5.0 wt%; at room temperature, the nylon 11 nanofibers prepared in Example 1 were placed in the culture solution for cultivation and taken out after 5 min. In this process, the acetic acid molecules induced the internal crystalline phase of the nylon 11 nanofibers to transform from a non-piezoelectric crystalline phase to a piezoelectric crystalline phase through protonation. Subsequently, the samples were dried in vacuum for 24 h to obtain an all-organic heterostructure piezoelectric polymer composite material, and the sample was marked as 5.0 wt%.
[0034] In order to verify the induction effect of acetic acid on the internal crystal transformation of nylon 11 nanofibers, two samples of "acid-treated nylon 11 nanofibers" and "ordinary nylon 11 film" were specially prepared: Preparation of acid-treated nylon 11 nanofibers: The nylon 11 nanofibers prepared in Example 1 were placed in an acetic acid solvent for incubation for 5 min, then taken out (the acetic acid completely submerged the nylon 11 nanofibers), and vacuum dried for 24 h to obtain acid-treated nylon 11 nanofibers.
[0035] Preparation of ordinary nylon 11 film: Place nylon 11 pellets in a hot press and hot press at a hot pressing temperature of 200°C and a pressure of 20 MPa to obtain an ordinary nylon 11 film.
[0036] Product structure characterization
[0037] Figure 1 This is a scanning electron microscope image of nylon 11 nanofibers in Example 1. Figure 1 It can be seen that the surface of nylon 11 fiber is smooth and defect-free, and the average fiber diameter is 270 nm.
[0038] Figure 2 The X-ray diffraction patterns of acid-treated and non-acid-treated nylon 11 nanofibers and ordinary nylon 11 films are shown in Figure 2. Figure 2 It can be seen that ordinary nylon 11 film only contains non-piezoelectric α crystals; nylon 11 nanofibers that have not been treated with acetic acid contain α crystals and a small amount of piezoelectric δ' crystals, of which the content of δ' crystals is 15.5 wt%; and nylon 11 nanofibers that have been treated with acetic acid mainly contain piezoelectric δ' crystals, of which the content of δ' crystals is 82.8 wt%.
[0039] Figure 3 This is a scanning electron microscope image of the all-organic heterostructure piezoelectric polymer composite material of Example 4. Figure 3 It can be seen that after the nylon 11 nanofibers are placed in the PCL culture medium for self-assembly, two-dimensional sheet-like PCL crystals grow epitaxially on the fiber surface. These crystals are periodically and vertically distributed on the surface of the nylon 11 nanofibers, forming a fully organic heterostructure.
[0040] Figure 4 The differential scanning calorimetry spectra of the acid-treated and untreated nylon 11 nanofibers and the all-organic heterostructure piezoelectric polymer composite materials of Examples 2-4 are shown. Figure 4 It can be seen that the melting point of nylon 11 nanofibers not treated with acetic acid is 181 °C, indicating that the crystals inside are mainly α crystals, while the melting points of nylon 11 nanofibers treated with acetic acid and the all-organic heterostructure piezoelectric polymer composites prepared in Examples 2-4 are increased to above 190 °C, which is the melting point of δ' crystals, indicating that the non-piezoelectric α crystals inside have been converted into piezoelectric δ' crystals.
[0041] Performance Testing
[0042] Piezoelectric devices are prepared using the nylon 11 nanofiber of Example 1 and the all-organic heterostructure piezoelectric polymer composite materials of Examples 2-4 as piezoelectric materials: the upper and lower surfaces of the piezoelectric material are respectively covered with copper metal electrodes, and metal wires are respectively connected from the electrode surfaces. Finally, the element is encapsulated by a polyimide or polydimethylsiloxane film to obtain a piezoelectric device.
[0043] Figure 5 The piezoelectric signal diagram of the piezoelectric device prepared based on the nylon 11 nanofiber of Example 1 and the all-organic heterostructure piezoelectric polymer composite material of Examples 2-4. Figure 5 It can be seen that compared with nylon 11 nanofibers, the all-organic heterostructure piezoelectric polymer composite material system exhibits higher piezoelectric properties, and the piezoelectric current and voltage increase with the increase of two-dimensional PCL crystals on the fiber surface.
[0044] Figure 6 The sensitivity of the piezoelectric device prepared based on the all-organic heterostructure piezoelectric polymer composite material in Example 4. Figure 6 It can be seen that the sensitivity of the all-organic heterostructure piezoelectric polymer composite material in the low pressure region (<4 kPa) is 670 mV / kPa, and the sensitivity in the high pressure region (>4 kPa) is 200 mV / kPa.
[0045] Figure 7 The service stability of the piezoelectric device prepared based on the all-organic heterostructure piezoelectric polymer composite material in Example 4. Figure 7 It can be seen that the piezoelectric performance of the piezoelectric device prepared based on the all-organic heterostructure piezoelectric polymer composite material has not decayed after 7000 cycles of operation, and has excellent service stability.
Claims
1. An all-organic heterostructure piezoelectric polymer composite material, characterized in that: It includes nylon 11 nanofibers and two-dimensional sheet-like PCL crystals epitaxially grown on the surface. The nylon 11 nanofibers contain piezoelectric crystal phases, and the content of the piezoelectric crystal phases in the fiber crystal structure is 70~90 wt%.
2. A method for preparing the all-organic heterostructure piezoelectric polymer composite material as claimed in claim 1, characterized in that: The preparation steps are as follows: (1) Preparation of nylon 11 nanofibers; (2) The PCL pellets were heated and dissolved in an acidic solvent to obtain a culture solution with a concentration of 0.1-5 wt%; at room temperature, nylon 11 nanofibers were placed in the culture solution for self-assembly for 3-10 min, and then dried to obtain an all-organic heterostructure piezoelectric polymer composite material.
3. The method for preparing the all-organic heterostructure piezoelectric polymer composite material according to claim 2, characterized in that: The acidic solvent is a mixed solvent composed of acetic acid and water in a volume ratio of (1-3):
1.
4. The method for preparing the all-organic heterostructure piezoelectric polymer composite material according to claim 2, characterized in that: The temperature for heating and dissolving is 50~80 ℃.
5. The method for preparing the all-organic heterostructure piezoelectric polymer composite material according to claim 2, characterized in that: The drying is vacuum drying.
6. The method for preparing the all-organic heterostructure piezoelectric polymer composite material according to any one of claims 2 to 5, characterized in that: Nylon 11 nanofibers were prepared by electrospinning or template method.
7. The method for preparing the all-organic heterostructure piezoelectric polymer composite material according to claim 6, characterized in that: The preparation process of the electrospinning method is: dissolving nylon 11 pellets completely in an organic solvent to obtain a spinning solution, and using an electrospinning device to prepare nylon 11 nanofibers.
8. The method for preparing the all-organic heterostructure piezoelectric polymer composite material according to claim 7, characterized in that: The organic solvent is a mixed solvent of trifluoroacetic acid and hexafluoroisopropanol in a volume ratio of (1-2):1; the spinning solution concentration is 5-10 wt%.
9. The method for preparing the all-organic heterostructure piezoelectric polymer composite material according to claim 7, characterized in that: The spinning solution was extruded at a rate of 0.1~1.0 mL / h in the electrospinning equipment, the applied voltage was 10~15 KV, the distance between the spinneret and the collector was 10~20 cm, and the nylon 11 nanofibers were collected using a high-speed roller with a rotation speed of 2000~5000 r / min; the internal ambient temperature of the spinning equipment was 20~30 ℃ and the humidity was 30~40%.
10. Use of the all-organic heterostructure piezoelectric polymer composite material as claimed in claim 1 in a pressure sensor, a nanogenerator, a wearable electronic device or a motion monitoring device.